2018
DOI: 10.1590/0074-02760170554
|View full text |Cite
|
Sign up to set email alerts
|

The status of cryptococcosis in Latin America

Abstract: Cryptococcosis is a life-threatening fungal infection caused by the encapsulated yeasts Cryptococcus neoformans and C. gattii, acquired from the environment. In Latin America, as occurring worldwide, C. neoformans causes more than 90% of the cases of cryptococcosis, affecting predominantly patients with HIV, while C. gattii generally affects otherwise healthy individuals. In this region, cryptococcal meningitis is the most common presentation, with amphotericin B and fluconazole being the antifungal drugs of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 186 publications
2
64
0
25
Order By: Relevance
“…Furthermore, previous studies have demonstrated that testosterone has multiple depressive effects on the immune system (McClelland et al, ; Pennell, Galligan, & Fish, ; Pinzan, Ruas, Casabona‐Fortunato, Carvalho, & Roque‐Barreira, ). These results support epidemiological data that indicate the higher occurrence rate of this disease in males (Firacative et al, ; Shaheen et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, previous studies have demonstrated that testosterone has multiple depressive effects on the immune system (McClelland et al, ; Pennell, Galligan, & Fish, ; Pinzan, Ruas, Casabona‐Fortunato, Carvalho, & Roque‐Barreira, ). These results support epidemiological data that indicate the higher occurrence rate of this disease in males (Firacative et al, ; Shaheen et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In a most recent large series of autopsies carried out in the low‐income countries, Mozambique and Brazil, over 40% of patients with cryptococcosis were immunocompetent (Hurtado et al, ). Among non‐HIV‐infected patients in Latin America, C. gattii VGII is reported as the main agent; in both HIV‐infected and non‐infected populations, most cases of cryptococcosis are reported in young males (Firacative, Lizarazo, Illnait‐Zaragozí, Castañeda, & Latin American Cryptococcal Study Group, ; Shaheen, Somayaji, Myers, & Mody, ).…”
Section: Introductionmentioning
confidence: 99%
“…The currently available antifungal drugs used to combat cryptococcosis consist of a combination of amphotericin B deoxycholate or liposomal amphotericin B and 5-fluorocytosine administered for 2 weeks. Fluconazole is recommended for use during the consolidation and maintenance phases, but this antifungal drug requires a long treatment course, which reduces patient compliance and/or tolerability [30, 31]. The treatments of cryptococcosis and other invasive fungal infections should display rapid fungicidal activity and completely eliminate the fungus from the host system.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high burden of cryptococcal meningitis related morbidity and mortality in resource limited settings, reviewed data on magnitude of cryptococcal antigenemia and its predictors is missing [22,23]. Hence, data is required on this field to inform policy makers for input to tailor intervention measures.…”
Section: Introductionmentioning
confidence: 99%